2021
DOI: 10.1111/gcb.15788
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of post‐drought recovery are strongly influenced by drought duration, frequency, post‐drought wetness, and bioclimatic setting

Abstract: Understanding vegetation recovery after drought is critical for projecting vegetation dynamics in future climates. From 1997 to 2009, Australia experienced a long‐lasting drought known as the Millennium Drought (MD), which led to widespread reductions in vegetation productivity. However, vegetation recovery post‐drought and its determinants remain unclear. This study leverages remote sensing products from different sources—fraction of absorbed photosynthetically active radiation (FPAR), based on optical data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 77 publications
(115 reference statements)
1
54
0
Order By: Relevance
“…Furthermore, resilience to a subsequent drought is probably decreased by drought frequency, that is the number of consecutive drought events. Several studies in fact support the notion that a higher drought frequency decreases both resistance (Bose et al, 2020; Xu et al, 2021) and recovery (Gao et al, 2018; Peltier & Ogle, 2019; Szejner et al, 2020; Jiao et al, 2021; Serra‐Maluquer et al, 2021). However, the opposite, that is a higher drought frequency leading to a higher resilience, has also been shown (Yao et al, 2022; see also the above section on adaptations shaping the resilience to a subsequent drought event).…”
Section: Effects Of Drought Legacies On Responses To Subsequent Droug...mentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, resilience to a subsequent drought is probably decreased by drought frequency, that is the number of consecutive drought events. Several studies in fact support the notion that a higher drought frequency decreases both resistance (Bose et al, 2020; Xu et al, 2021) and recovery (Gao et al, 2018; Peltier & Ogle, 2019; Szejner et al, 2020; Jiao et al, 2021; Serra‐Maluquer et al, 2021). However, the opposite, that is a higher drought frequency leading to a higher resilience, has also been shown (Yao et al, 2022; see also the above section on adaptations shaping the resilience to a subsequent drought event).…”
Section: Effects Of Drought Legacies On Responses To Subsequent Droug...mentioning
confidence: 87%
“…Lindberg and Bengtsson (2006), Coyle et al (2017); 8. Saatchi et al (2013), Kannenberg, Novick, et al (2019), Jiao et al (2021), Senf et al (2021); 9. Griffin‐Nolan et al (2018), Sala et al (2012), Petrie et al (2018), DeVries et al (2016), Yang et al (2018), DeVries et al (2019), Wigneron et al (2020); 10.…”
Section: Defining and Characterizing Drought Legaciesmentioning
confidence: 99%
“…Previous studies have reported that long‐term drought leads to a prolonged recovery period of vegetation, in which the rate of increase of GPP is significantly smaller than the recovery after short‐term drought (Hoover & Rogers, 2016; Li et al, 2019). Furthermore, long‐term drought could result in an incomplete GPP recovery, i.e., GPP could not restore to pre‐drought levels (Jiao et al, 2021). All those above negative effects result in a larger CV in GPP under longer CED.…”
Section: Discussionmentioning
confidence: 99%
“…Increased exposure of forests to high‐severity fire will undoubtably increase CO 2 emissions (Bowman et al., 2021) and reduce stored carbon across vast areas of south‐eastern Australia (Fairman et al., 2022). The impacts of these shifts in fire regimes will be compounded further by drought, which will likely decrease ecosystem resistance and impair ecosystem recovery (Enright et al., 2015; Jiao et al., 2021; Nolan et al., 2021). Targeted management of ecosystems aimed at increasing resistance and resilience will be required to mitigate the elevated risk of high‐severity fires over the region (Bowman, Kolden, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%